Electron detection with CdTe and GaAs sensors using the charge integrating hybrid pixel detector JUNGFRAU. (1st January 2022) - Fröjdh, E.; Abrahams, J.P.; Andrä, M.; Barten, R.; Bergamaschi, A.; Brückner, M.; Chiriotti, S.; Dinapoli, R.; Greiffenberg, D.; Hinger, V.; Lovacik, L.; King, T.; et al.
Abstract: Speed, dynamic range, and radiation hardness make hybrid pixel detectors suitable image detectors for diffraction experiments. At synchrotrons and X-ray free electron lasers they are ubiquitous. However, for electron microscopy their spatial resolution is limited by multiple scattering in the sensor layer. In this paper we examine the use of two high Z sensor materials: CdTe and GaAs, as a way to mitigate this problem. The sensors were bonded to a JUNGFRAU readout chip which is a charge integrating hybrid pixel detector developed for use at X-ray free electron lasers. Using in-pixel gain switching, it can detect single particles down to 2 keV while maintaining a dynamic range of 120 MeV/pixel/frame. The characteristics of JUNGFRAU, besides being a capable detector, make it a good tool for sensor characterization since we can measure dark current and energy deposition per pixel. The high Z material shows better spatial resolution than silicon at 200 and 300 keV, however, their practical use with integrating detectors is still limited by material defects.